Measuring the self-correction of brain morphology in pre-metamorphic Xenopus laevis tadpoles by examining markers of brain tissue differentiation and cerebrospinal fluid flow - Barry, Maura J. (Tufts University. Tisch Library., 2018)
The McLaughlin lab is working to elucidate the underlying mechanisms that direct the self-correction of malformed tissues in the heads of Xenopus laevis tadpoles, with the ultimate goal of supporting the discovery of novel treatments for correcting human craniofacial birth defects. To help this objective, my project focused on determining whether brain tissue in pre- metamorphic tadpoles with craniofacial defects is properly differentiated prior to and after the life stages where malformed craniofacial tissues are known to correct. The second part of my project was to examine the cerebrospinal fluid flow in the brains to determine whether or not there was a blockage of flow in the malformed brains, and whether this is corrected over time as well. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.